The critical relationship between tacrolimus levels, acute kidney injury, and early chronic lung allograft dysfunction - Hauber, Roman; Kohlhepp, Luca; Briegel, Ignaz; Veit, Tobias; Barton, Jürgen; Meiser, Bruno; Schneider, Christian; Kauke, Teresa; Hatz, Rudolf; Hoechter, Dominik J.; Kneidinger, Nikolaus; Behr, Jürgen (Frontiers in Transplantation, 2026)
BackgroundBased on clinical observations, we hypothesized that tacrolimus (TAC) exposure and acute kidney injury (AKI) are associated with the development of chronic lung allograft dysfunction (CLAD) after lung transplantation (LTx).MethodsOf 827 lung transplant recipients treated between 2000 and 2018, 509 with complete data sets from the University Hospital of Munich (LMU) were included in this study. In the context of a 10% reduction in FEV1 (CLAD10), tacrolimus and renal function were examined descriptively, inferentially, and through confounder analysis with regard to the occurrence of CLAD10.ResultsOf 509 LTx patients, 67 (13%) died within the first 2 years after LTx. Among these 67 patients, 38 (57%) developed CLAD10 within 2 years of LTx. In these patients, we observed a temporal pattern characterized by a peak in TAC levels, followed by AKI, and subsequently subtherapeutic TAC concentrations, which occurred a few weeks before the onset of CLAD10. The confounder analysis demonstrated a significant influence of renal failure and tacrolimus fluctuations on the hazards ratio for developing CLAD10.ConclusionOur data suggest that a transient decline in TAC serum concentrations, often caused by a TAC-induced AKI, may trigger the onset of CLAD10 and subsequently elevate the risk of premature death.